Impacts of Arizona’s SB 1070 on Mexican American Students’ Stress, School Attachment, and Grades - Orozco, Richard A.; López, Francesca (Education Policy Analysis Archives, 2015)
Understanding the impacts of immigration legislation on Mexican ethnic students who are citizens of the United States is needed. This study investigates how passage of Arizona’s anti-immigration law, SB 1070, in 2010 bears upon the schooling experiences of Mexican American high school students. Applying Meyer’s Minority Stress Model as the theoretical foundation for this work, the authors ultimately explore, 1) whether perceived discrimination along with acculturation, racial phenotype, familiarity and stress associated with SB 1070 influence school grades, and 2) the effects of SB 1070 stress on the school attachment of Mexican American high school students. The authors find that perceived discrimination and skin color are both negatively related to grades, whereas maintaining Spanish is positively related to grades, and SB 1070 stress and its effects are dependent upon levels of perceived discrimination. Likewise, while the authors find no relation of SB 1070 stress to school attachment, they do find that this relationship is moderated by perceived discrimination such that school attachment decreases as stress associated with SB 1070 increases for individuals with lower perceived discrimination. For individuals with high levels of perceived discrimination, there is a positive association between school attachment and SB 1070 stress. By impacting their acculturative stress, Arizona’s SB 1070 has further upset an already precarious schooling experience for Mexican American students.